Analysis Of Character Building Values In Turning Red - Tawali, Tawali; Suhaili, Muhamad (Lembaga Penelitian dan Pendidikan Mandala, 2023)
In the field of education, in Indonesia there are many moral crises occurring. Considering the existence of a moral degradation, in this case, the government implements the education of the character which will serve as a solution to the form and reconstitutes the behavior of the pupils to have a noble character in according to the character of the nation.The purpose of this research is to find out character building values in The Turning Red movie. The researcher used theory of Zaim El Mubarok that Character Building Values divided into two groups. There are (1) to recognize the types of character building values Turning Red movie. (2) to recognize the percentages of character building values in The Turning Red movie, (3) to describe the implication of character building values in The Turning Red movie. This research, the researcher used the library research which applies descriptive qualitative approach. The primary data sources were “Turning Red movie” and it’s script.The secondary sources were taken from other books and related references which supported and concerned the primary data. The researcher used content analysis to analyze the data. The result of this study shows that were are two groups to analysis the character building values. There are values of being and values of giving. The values of being, namely: (1) Honesty, (2) brave, (3) peace, (4) confidence and potential, (5) self-dicipline and moderation self, (6) purity. Then values of giving, namely (1) loyalty and trust worthiness, (2) respect, (3) love and affection, (4) sensibility and not selfishness, (5) kind and friendly, (6) fair and humanist.